The Effect Of Extra Virgin Olive Oil To Increase Endogeneous Antioxidant And PlGF In Preeclampsia Rat Model - Yulia Silvani (Journal of Global Pharma Technology, 2019)
Background: Preeclampsia is a special disease in pregnancy with oxidative stress as one of its pathogenesis pathways, suspected that it can interfere the process of angiogenesis and negatively impacts the fetus and maternal wellbeing. Objective: This study aimed to determine effect of EVOO as a strong exogenous antioxidant to increase SOD activity and GSH level in accordance with improvement on PlGF level as an angiogenesis factor in preeclampsia rat model. Method: This research consisted of five groups; negative control, positive control (preeclampsia rat model), doses 1, 2, and 3 that were preeclampsia rats given EVOO in 3 different doses (0.5 mL/day, 1 mL/day and 2 mL/day respectively). Blood pressure measurements were carried out at the 12th, 15th, and 19th day of pregnancy. After sacrificed, placentas were collected to determine SOD activity and GSH level either maternal plasma to determine PlGF level. Results: Result of this study showed that there was a reduction of GSH (p=0.02) and PlGF (p=0.233) level between negative and positive control group meanwhile SOD activity seem increased (p=0.049). There were significant differences among positive control and dose 1 in SOD activity (p=0.008), dose 3 in GSH level (p=0.000), both dose 1 (p=0.017) and 2 (p=0.000) in PlGF level. Conclussion: Administration of EVOO increased SOD and GSH in all three doses groups, while there was a decrease in PlGF at dose 3. EVOO had been shown to be a potential antioxidant in preeclampsia through increased SOD activity and GSH level, at once modulate angiogenesis through increased PlGF level.Keywords: Preeclampsia, EVOO, SOD, GSH, PlGF, Antioxidant, Oxidative stress, Angiogenesis